Significance of Micro-organisms in Afforestation Programmes in Arid Zone - Rao, A V; Tarafdar, J C (Annals of Arid Zone, 2016)
Trees play a significant role in sustaining the productivity in arid zones. But their establishment and growth in arid zone are poor because of harsh climate coupled with low fertility of light sandy soils. The effects of inoculating seeds of various trees with efficient strains of Rhizobium and inoculating soil with VAM-fungi, alone or in combination, appear promising. Further. dual inoculation of trees helps in mitigloneating the adverse effects of salinity. Nitrogen fixed in tree legumes was found to be transferred to the non-legumes when grown either in ilvopastoral or agroforestry systems.